Pengaruh Omni Channel terhadap Sales Performance dengan CRM sebagai Variabel Mediasi pada UMKM Sukabumi: indonesia - Samiono, Bambang Eko; Wijaya, Indra Satria Ari (UII, 2026)
This study examines the paradoxical phenomenon of declining transaction values among MSMEs in Sukabumi despite a significant increase in the number of businesses and widespread participation in the Indonesian government's “Go Digital” program, yet their sales performance has not increased proportionally. This study aims to analyze the impact of Omni Channel l implementation on Sales Performance, with Customer Relationship Management (CRM) as a mediating variable. A quantitative approach using Structural Equation Modeling (SEM) with AMOS was applied. The population consisted of 110 MSMEs in Sukabumi who had participated in digital literacy training, specifically in internet marketing through WhatsApp Business. Data were collected using non-probability sampling and measured through 11 indicators. The results show that Omni Channel l has a significant direct effect on both CRM (β = 0.572, p < 0.001) and Sales Performance (β = 0.528, p = 0.002). However, CRM does not have a significant direct effect on Sales Performance (β = 0.272, p = 0.075). Furthermore, the indirect effect of Omni Channel l on Sales Performance through CRM was not supported. The structural model explains 51.8% of the variance in Sales Performance and 32.7% in CRM. These findings indicate that, in the context of MSMEs in Sukabumi, the implementation of simple and practical Omni Channel l, especially through WhatsApp Business, plays a more critical role in improving sales performance than formal CRM practices. The absence of a mediating effect of CRM suggests that most MSMEs operate at an operational stage where structured CRM systems have not been optimally implemented or are not yet necessary.